An Epidemic of Flying Heads in a Melanau Community in Sarawak, Malaysia - Appleton, Ann (Universiti Malaysia Sarawak (UNIMAS), 2010)
In May 2001 a spate of reported sightings of ulou pesilieng, or flying heads, occurred in the Melanau villages around Mukah, Sarawak, accompanied by reports of sick children and generalized anxiety amongst the inhabitants. Historically, this phenomenon was associated with the Melanau a-bayoh (shaman of the old animistic religion). Under the influence of their familiars, some of these persons (the flying head a-bayohs) were believed to detach from their bodies at night and roam the villages, seeking to satisfy an appetite for human blood. This outbreak seemed surprising, firstly because in the whole of the Melanau territories only a handful of a- bayohs - almost all of them elderly men, still practised. The majority of the Melanau had given up the old religion and converted to either Islam or Christianity over thecourse of the previous century. Secondly, anthropologist Stephen Morris who carried out long-term research in the Melanau kampongs in the middle of the twentieth century reports that people at that time asserted that such incidents no longer occurred. What circumstances then had triggered this belated return of the ulou pesilieng and created the agitation and alarm that ensued? The analysis draws on the work of Turner and Douglas, as well as Jungian and post-Jungian perspectives, to present an argument that ulou pesilieng embody characteristics that identify them as culturally constructed artefacts with connections to a historically specific Melanau life world and a particular set of social relations. In this scenario, the reappearance of the ulou pesilieng can be explained as both a reflection on and response to critical cultural changes taking place in the Melanau life world at the beginning of the 21st century. Reports of ulou pesilieng and other similarly horrifying cultural phenomena have occurred during at least two other periods in recorded Melanau history, suggesting that such phenomena may be prevalent at times of societal transition.